2018
DOI: 10.1002/advs.201800875
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable Hydrogels Mediate Cofactor‐Assisted Activation of Biomarker‐Responsive Drug Delivery via Positive Feedback for Enhanced Tissue Regeneration

Abstract: The targeted and simultaneous delivery of diverse cargoes with vastly different properties by the same vehicle is highly appealing but challenging. Here, a bioactive nanocomposite hydrogel based on hyaluronic acid and self‐assembled pamidronate‐magnesium nanoparticles for the localized elution and on‐demand simultaneous release of bioactive ions and small molecule drugs is described. The obtained nanocomposite hydrogels exhibit excellent injectability and efficient stress relaxation, thereby allowing easy inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 49 publications
2
112
0
Order By: Relevance
“…In particular, the combination of BMP‐2 and SF@TA@HA exhibited the highest ALP expression of MSCs. A similar trend was observed by using von Kossa and alizarin red staining of the hydrogel histological sections . The increased staining intensity provided obvious evidence of cell‐mediated calcium mineral deposition and demonstrated that MSCs were more inclined to differentiate into osteoblasts.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In particular, the combination of BMP‐2 and SF@TA@HA exhibited the highest ALP expression of MSCs. A similar trend was observed by using von Kossa and alizarin red staining of the hydrogel histological sections . The increased staining intensity provided obvious evidence of cell‐mediated calcium mineral deposition and demonstrated that MSCs were more inclined to differentiate into osteoblasts.…”
Section: Resultssupporting
confidence: 79%
“…Because the regeneration of bone tissue is often complicated in vivo due to the presence of inducing factors, bone morphogenetic protein‐2 (BMP‐2) is used as an osteoinductive protein to enhance the osteogenic differentiation of MSCs in vitro, which provides a reasonable reference for analyzing the effect of SF@TA@HA on in vitro and in vivo osteogenesis. The in vitro osteogenic differentiation of MSCs was characterized by the expression of alkaline phosphatase (ALP, Figure A), an early indicator that assess osteoblastic metabolic activity . Compared to the pure SF control group, significantly enhanced ALP staining and activity were observed in the SF@TA@HA group after 14 d of culture, suggesting the upregulation of ALP by SF@TA@HA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] Compared to various nanochemical polymers (upconversion nanotransducer-based nanocomplexes, nanocomposite hydrogels, or supramolecular hydrogels), TFNA not only possesses good biocompatibility and biodegradability and the ability to permeate cells but can also be functionalized via modification with DNA fragments, RNAs, polypeptide monomers, and small-molecule drugs. [31][32][33][44][45][46] In our previous studies, we found that TFNA can enhance the proliferation and migration of chondrocytes and maintain their morphology at an optimum concentration of 250 nmol·L −1 . 21,22 Upon consideration of these characteristics, TFNA was used in combination with wogonin, a naturally occurring flavonoid with various biological properties, such as anti-inflammatory and anti-cancer activity.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, it has been reported that collagen matrix for tendon regeneration has good biocompatibility and mechanical properties, promoting cell adhesion and growth, and thereby behave as an ideal biomaterial for tissue regeneration [18]. Collagen matrix has a typical three-dimensional (3-D) crosslinking network with high drug/cell embedding rates and local maintenance of drugs/cells [19,20]. Once encapsulated into the collagen matrix and injected into the tissues, cells, drugs, or EVs can be captured by the cross-linking network and released in a sustained manner [11,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%